2013
DOI: 10.1111/1758-2229.12071
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with Microcystis colonies differ from free‐living communities living in the same ecosystem

Abstract: The search for a better understanding of why cyanobacteria often dominate phytoplankton communities in eutrophic freshwater ecosystems has led to a growing interest in the interactions between cyanobacteria and bacteria. Against this background, we studied the location of bacteria within Microcystis colonies, and compared the structural and phylogenetic diversity of Microcystis-attached and free-living bacterial communities living in the same French lake, the Villerest reservoir. Using transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
91
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 56 publications
(70 reference statements)
14
91
1
Order By: Relevance
“…The order Chthoniobacterales (in the phylum Verrucomicrobia) was also found as a bloom biomarker, consistent with previous studies that observed this taxon in association with Anabaena blooms (Louati et al, 2015). Other studies have reported specific association between Verrucomicrobia and Cyanobacteria, suggesting that members of this phylum might assimilate cyanobacterial metabolites (Parveen et al, 2013;Louati et al, 2015). We also found N 2 -fixing members of Rhizobiales order as bloom biomarkers.…”
Section: Discussionsupporting
confidence: 91%
“…The order Chthoniobacterales (in the phylum Verrucomicrobia) was also found as a bloom biomarker, consistent with previous studies that observed this taxon in association with Anabaena blooms (Louati et al, 2015). Other studies have reported specific association between Verrucomicrobia and Cyanobacteria, suggesting that members of this phylum might assimilate cyanobacterial metabolites (Parveen et al, 2013;Louati et al, 2015). We also found N 2 -fixing members of Rhizobiales order as bloom biomarkers.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, all these communities were highly specialized, and as there were major differences among communities, we conclude that they were affected by the phycosphere conditions created by cyanobacteria. Others have also observed the selection of specific bacterial species within the Microcystis phycosphere by comparing Microcycstis -attached bacteria (phycosphere bacteria) with other microbial communities living in the same aquatic ecosystem [11], [13].…”
Section: Resultsmentioning
confidence: 99%
“…Cyanobacterial blooms, especially Microcystis blooms, are frequently found in eutrophic freshwater ecosystems and can pose notable risks to ecological and human health [35]. Bacterial communities associated with marine phytoplankton blooms [2, 67] and bloom-forming freshwater phytoplankton in growing stage [1, 8] have also received considerable attention. In contrast, only a few studies have examined the bacterial community composition in response to the breakdown of algal blooms in freshwater lakes [911].…”
Section: Introductionmentioning
confidence: 99%